Outer membrane vesicles: A bacterial-derived vaccination system - Lieberman, Linda A. (Frontiers in Microbiology, 2022)
Outer membrane vesicles (OMVs) are non-living spherical nanostructures that derive from the cell envelope of Gram-negative bacteria. OMVs are important in bacterial pathogenesis, cell-to-cell communication, horizontal gene transfer, quorum sensing and in maintaining bacterial fitness. These structures can be modified to express antigens of interest using glycoengineering and genetic or chemical modification. The resulting OMVs can be used to immunize individuals against the expressed homo- or heterologous antigens. Additionally, cargo can be loaded into OMVs and they could be used as a drug delivery system. OMVs are inherently immunogenic due to proteins and glycans found on Gram negative bacterial outer membranes. This review focuses on OMV manipulation to increase vesiculation and decrease antigenicity, their utility as vaccines, and novel engineering approaches to extend their application.